Expectancies and motivations to attend an informal science lecture series - AbiGhannam, Niveen (Institutional Knowledge at Singapore Management University, 2016)
This study explored the expectancies and motivations that prompt audiences to attend a university science lecture series. The series features talks by science experts from the host campus and around the USA. Each lecture typically attracts between 300 and 600 attendees, including middle and high school student groups, university students, and families and adults from the area. We conducted 47 semi-structured interviews with attendees in order to evaluate their expectancies and motivations. A template analysis of the interviews was grounded in social cognitive and self-determination theories. Results suggest that participants were mostly driven by intrinsic motivations and acquired strong sensory outcome expectancies, such as novelty and activity. Participants also held physical outcome expectancies, such as social expectancies, though to a lesser extent. Both intrinsic and extrinsic motivations to attend the lecture series were associated with expectancies held prior to the event. Of those expectancies, the novelty, entertainment, and social outcomes were dominant. Other noteworthy outcome expectancies include status and self-reactivity. Parents and teachers held outcome expectancies, not only for themselves, but also for their children and students who attended the talks with them.